2003
DOI: 10.1590/s0100-41582003000100001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic linkage map of Phaseolus vulgaris and identification of QTLs responsible for resistance to Xanthomonas axonopodis pv. phaseoli

Abstract: Common bean (Phaseolus vulgaris) cultivars with a high degree of resistance to Xanthomonas axonopodis pv. phaseoli (Xap) are not available in Brazil. Despite many studies, a low degree of resistance to Xap continues to exist due to its complex genetic inheritance, which is not well known. The objectives of this research were to complement a common bean genetic map based on the cross between a susceptible genotype 'HAB-52' and a resistant genotype 'BAC-6', and to map and analyze genomic regions (quantitative tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 18 publications
3
13
0
Order By: Relevance
“…This result is expected due to the type of evaluation and the period in which resistance was assessed on pods, the more advanced ontogenic stage of pod formation. These estimates of low linear correlation values between DL and the other components of resistance also agree with previous studies on the complex heritage for pod resistance to CBB, which showed that the genes that control resistance on leaves of the snap beans are not the same that control resistance on pods (Arnaud-Santana et al 1994;Rodrigues et al 1999;Santos et al 2003).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…This result is expected due to the type of evaluation and the period in which resistance was assessed on pods, the more advanced ontogenic stage of pod formation. These estimates of low linear correlation values between DL and the other components of resistance also agree with previous studies on the complex heritage for pod resistance to CBB, which showed that the genes that control resistance on leaves of the snap beans are not the same that control resistance on pods (Arnaud-Santana et al 1994;Rodrigues et al 1999;Santos et al 2003).…”
Section: Resultssupporting
confidence: 90%
“…phaseoli, as expressed by molecular biology data and by reactions observed after inoculation of differential hosts with the same isolate (Mahuku et al 2006;Márquez et al 2007;Mkandawire et al 2004). While investigating regions of the bean plant genome related to CBB resistance, Santos et al (2003) observed that the genes that confer resistance to Xap on leaves differ from those that confer resistance on pods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six QTLs in F 3 plants resulting from the BAC-6 and HAB-52 cross were identified by Santos et al (2003). Five of these QTLs were associated with resistance of leaves and one of pods, with a phenotypic variation from 12.7 to 68.7% for leaf and 12.9% for pod resistance.…”
Section: Resultsmentioning
confidence: 99%
“…These pathogens are widespread in the producing regions, causing yield losses, especially when stimulated by favorable environmental conditions such as high temperatures (Theodoro 2004) The first pathogen symptoms of common bacterial blight appear on the shoot, consisting primarily of small watersoaked areas in the leaves, evolving to necrosis and imperfections in the seeds such as discoloration of the hilum, yellow spots, and wrinkling of the seed coat, which can reduce yields by 10 to 70% (Diaz et al 2001, Bianchini et al 2005. The inheritance of resistance to this pathogen is genetically complex, described by several authors as oligogenic or polygenic (Kelly et al 2003, Santos et al 2003, Manzanera et al 2005. According to Zapata et al (2010), Ferreira and Grattapaglia (2003), and Marquez et al (2007), the number of genes, degrees and interactions involved in the expression of this trait may vary.…”
Section: Introductionmentioning
confidence: 99%